Recurrent systemic embolism caused by descending thoracic aortic mural thrombus in a young cannabis abuser. Issue 3 (March 2016) - Noel, Antoine; Le Ven, Florent; Gilard, Martine; Bressollette, Luc; Castellant, Philippe; Vinsonneau, Ulric; Paleiron, Nicolas; Mansourati, Jacques
Abstract: Aortic mural thrombi are a rare cause of peripheral arterial embolic events. We report the case of a young man with prior history of Buerger's disease and marijuana abuse. He presented visceral infarctions due to descending thoracic aortic mobile pedunculated thrombus with complex atherosclerosis. Cannabis was stopped, intravenous heparin and vitamin K antagonist (VKA) therapies were administered. At 3-month follow-up, he was free of thromboembolic events and aortic imaging normalized. Optimal treatment of embolized aortic thrombus remains controversial, but systemic anticoagulation is widely accepted as the first-line therapy. <Learning objective: Arteritis due to cannabis has been well reported and arterial proximal atherosclerosis lesions may also be present. Aortic mural thrombi predominantly occur in pathological aortic segments at the site of atherosclerotic plaque. As shown in this case, short-term favorable outcomes can be obtained with oral anticoagulation and the interruption of marijuana abuse.>